Examining the Performance of Portable Cold-storage Box Based on Phase-change Technology - Zhang Wenyu; Zhao Changying (Zhileng xuebao)
Temperature failure at the end of cold-chain transportation is common. Based on phase-change technology, a cold energy storage box suited for the end of cold-chain transport below -18 ℃ was developed. The temperature field characteristics and cold-storage performance of the cold-storage box under the influence of the environmental temperature, the thickness of the vacuum insulated panel (VIP), relative positions of the phase-change material (PCM) and VIP, type of PCM, and other parameters were examined. The study revealed that the cold-storage box had strong immunity to variations in the ambient temperature, and the maximum effective cold preservation time can be extended to 29.26 h when assembling the vacuum insulated panels. When the VIPs were placed on the outer layer of the corresponding PCM panels, the effective cold preservation period increased by 54.3%. Four types of organic PCMs with different phase-change temperatures were examined for use in cold-storage boxes. It was determined that 2-octanone with a phase transition temperature of -21.55 ℃ had the optimal performance in terms of cold preservation time, uniformity coefficient, and power consumption. The bottom plate had the greatest impact on the overall cold-storage capacity as evidenced by its 0.454 individual plate factor.